Effect of parental and ART treatment characteristics on perinatal outcomes. Issue 6 (16th April 2021) - Pontesilli, M; Hof, M H; Ravelli, A C J; van Altena, A J; Soufan, A T; Mol, B W; Kostelijk, E H; Slappendel, E; Consten, D; Cantineau, A E P; van der Westerlaken, L A J; van Inzen, W; et al.
Abstract: STUDY QUESTION: Do parental characteristics and treatment with ART affect perinatal outcomes in singleton pregnancies? SUMMARY ANSWER: Both parental and ART treatment characteristics affect perinatal outcomes in singleton pregnancies. WHAT IS KNOWN ALREADY: Previous studies have shown that singleton pregnancies resulting from ART are at risk of preterm birth. ART children are lighter at birth after correction for duration of gestation and at increased risk of congenital abnormalities compared to naturally conceived children. This association is confounded by parental characteristics that are also known to affect perinatal outcomes. It is unclear to which extent parental and ART treatment characteristics independently affect perinatal outcomes. STUDY DESIGN, SIZE, DURATION: All IVF clinics in the Netherlands (n = 13) were requested to provide data on all ART treatment cycles (IVF, ICSI and frozen-thawed embryo transfers (FET)), performed between 1 January 2000, and 1 January 2011, which resulted in a pregnancy. Using probabilistic data-linkage, these data (n = 36 683) were linked to the Dutch Perinatal Registry (Perined), which includes all children born in the Netherlands in the same time period (n = 2 548 977). PARTICIPANTS/MATERIALS, SETTING, METHODS: Analyses were limited to singleton pregnancies that resulted from IVF, ICSI or FET cycles. Multivariable models for linear and logistic regression were fitted including parental characteristics as well as ART treatment characteristics. Analyses were performed separately for fresh cycles and for fresh and FET cycles combined. We assessed the impact on the following perinatal outcomes: birth weight, preterm birth below 37 or 32 weeks of gestation, congenital malformations and perinatal mortality. MAIN RESULTS AND THE ROLE OF CHANCE: The perinatal outcomes of 31 184 out of the 36 683 ART treatment cycles leading to a pregnancy were retrieved through linkage with the Perined (85% linkage). Of those, 23 671 concerned singleton pregnancies resulting from IVF, ICSI or FET. Birth weight was independently associated with both parental and ART treatment characteristics. Characteristics associated with lower birth weight included maternal hypertensive disease, non-Dutch maternal ethnicity, nulliparity, increasing duration of subfertility, hCG for luteal phase support (compared to progesterone), shorter embryo culture duration, increasing number of oocytes retrieved and fresh embryo transfer. The parental characteristic with the greatest effect size on birth weight was maternal diabetes (adjusted difference 283 g, 95% CI 228–338). FET was the ART treatment characteristic with the greatest effect size on birth weight (adjusted difference 100 g, 95% CI 84–117) compared to fresh embryo transfer. Preterm birth was more common among mothers of South-Asian ethnicity. Preterm birth was less common among multiparous women and women with 'male factor' as treatment indication (compared to 'tubal factor'). LIMITATIONS, REASONS FOR CAUTION: Due to the retrospective nature of our study, we cannot prove causality. Further limitations of our study were the inability to adjust for mothers giving birth more than once in our dataset, missing values for several variables and limited information on parental lifestyle and general health. WIDER IMPLICATIONS OF THE FINDINGS: Multiple parental and ART treatment characteristics affect perinatal outcomes, with birth weight being influenced by the widest range of factors. This highlights the importance of assessing both parental and ART treatment characteristics in studies that focus on the health of ART-offspring, with the purpose of modifying these factors where possible. Our results further support the hypothesis that the embryo is sensitive to its early environment. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by Foreest Medical School, Alkmaar, the Netherlands (grants: FIO 1307 and FIO 1505). B.W.M. reports grants from NHMRC and consultancy for ObsEva, Merck KGaA, iGenomics and Guerbet. F.B. reports research support grants from Merck Serono and personal fees from Merck Serono. A.C. reports travel support from Ferring BV. and Theramex BV. and personal fees from UpToDate (Hyperthecosis), all outside the remit of the current work. The remaining authors report no conflict of interests. TRIAL REGISTRATION NUMBER: N/A.